Eskplorasi Bunga Fuschia Menggunakan Teknik Ruffle dan Cording pada Busana Pesta - Maheynna Galuh Phytaloka Putri Alamsyah, Khrisna; Inang Prihatina, Yuhri (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Fuchsia is a flower with a unique shape like "Indian Earrings" and the beauty of contrasting colors and two harmonious color patterns. The research objectives are 1) To describe the process of exploring fuchsia flowers as decoration for party clothing. 2) Find out the results of the exploration of the Fuchsia flower by applying Manipulating Fabric Ruffles and Cording to party clothing. This research method uses the Double Diomond Model which has 4 stages, namely: Discover, the stage of exploring the source of inspiration for the Fuchsia flower, determining the Manipulating Fabric which is made for young women and men with an elegant and classic type. Define, the stage of identifying sources of ideas in presenting Moodboard concepts, and creating illustration designs. Develop, the trial stage through prototyping, creating clothing with detailed clothing, using materials that are not much different in texture from the main material, after that applying Manipulating Fabric Ruffle and Cording techniques. Deliver is the stage of conveying the results of the trial, which shows that making party clothes requires looking at the technique of applying decorative motifs, determining colors and silhouettes to match the inspirational concept that has been created. The results of the research are the results of the suitability of the Manipulating Fabric Ruffle and Cording silhouette shapes in women’s and men’s party wear, inspired by the Fuchsia flower and displayed in the work event.